Isolated Optic Nerve Glioma in Children With and Without Neurofibromatosis: Retrospective Characterization and Analysis of Outcomes. (May 2018) - Hamideh, Dima; Hoehn, Mary Ellen; Harreld, Julie H.; Klimo, Paul D.; Gajjar, Amar; Qaddoumi, Ibrahim
Isolated optic nerve glioma is a rare tumor with no consensus for the best therapeutic approach. Therefore, tumor control and preservation of visual function remain a challenge. In this retrospective study, we describe our experience over 30 years in a single-institutional cohort of children with isolated optic nerve glioma, focusing on treatments and visual outcomes. Seventeen children were followed for a median period of 8 years (range, 2-22 years). Diagnosis was based on typical neuroradiologic findings, and 3 patients had histologic confirmation of their tumors. In our study, conservative management preserved the vision of most patients with neurofibromatosis type 1 (NF1). NF1-related optic nerve gliomas were less often treated but were associated with a lower probability of progression and with occasional spontaneous regression. Sporadic tumors more frequently exhibited aggressive clinical behavior with a higher propensity for posterior extension, often requiring surgical intervention.